Characterization and phylogenetic analysis of the complete mitochondrial genome of a tropical sea cucumber, Holothuria fuscocinerea. Issue 3 (2nd July 2020) - Cheng, Chuhang; Wu, Feifei; Ren, Chunhua; Jiang, Xiao; Wu, Xiaofen; Huang, Wen; Hu, Chaoqun
Abstract: In this study, the mitochondrial genome (mitogenome) of Holothuria fuscocinerea was unraveled to be 15, 890 bp in length, containing 13 protein-coding genes (PCGs), 22 tRNA genes, and 2 rRNA genes. The PCGs were initiated by four initiation codons (ATG, TAC, ATC, and ATA). Only one PCG ( nad6 ) and five tRNA genes ( tRNA Ser(UCN), tRNA Gln, tRNA Ala, tRNA Val, and tRNA Asp ) were encoded on the light chain, and the other genes were encoded on the heavy chain. A phylogenetic tree constructed with 16S rRNA sequences showed that H. fuscocinerea is most closely related to H. leucospilota .